Strategic Program Innovation to Optimize Islamic Religious Education in Schools - Juliani; Arif Akbar; Amanda Rezeki Padila; Dinda Aulia Prastiwi; Dwi Andini (Yayasan Zia Salsabila, 2023)
Islamic Religious Education (PAI) in schools has an important role in shaping the character and spirituality of students. However, the challenges of the digital era and social dynamics demand strategic program innovations to optimize PAI learning. This article discusses various innovations that can be applied, such as the integration of technology in learning, the development of a relevant curriculum, the improvement of teacher competence, and the application of active learning methods. By adopting these strategies, PAI is expected to be more effective in forming a generation that is faithful, noble, and able to face the challenges of the times.